Оптимальне завантаження генеруючих потужностей енергосистеми за умови експлуатації сонячних електростанцій із системами акумулювання - Shulzhenko S.V.; Nechaieva T.P.; Buratynskyi I.M. (General Energy Institute of the National Academy of Sciences of Ukraine, 2021)
Due to the increase in the share of electricity production at solar photovoltaic power plants (PV-plants), with a decrease in consumption and low flexibility of the power system, forced dispatch restrictions of generating capacities are already occurring. The problem of the emergence of a power surplus with an increase in the capacity of PV-plant can be solved by introducing a battery energy storage system (BESS) into its structure. The purpose of this study is to develop a mathematical model for the joint operation of a PV-plant and BESS for the formation of characteristic hourly daily power profiles for the supply of electrical energy to the power system. With the subsequent assessment of the impact of such hybrid PV-plants on changing the loading modes of traditional generating capacities in the Integrated power system of Ukraine.The proposed mathematical model for the joint operation of a PV-plant and BESS is, in fact, an algorithm for controlling such a hybrid PV-plant. The main principle of which is that during the period of maximum solar irradiation, the batteries are charged to the maximum possible level, which corresponds to the available capacity, and if the volume of BESS produced at the PV-plant is less than the available capacity, then all the generated electrical energy is accumulated for further discharge. Thus, the main modes of joint operation of a PV-plant and BESS are distinguished: mode No. 1 – when all PV generated electrical energy is charged with subsequent discharge; mode No. 2 – only a part of PV generated electrical energy is transferred in time, and the other part is supplied to the power system directly.Based on the developed mathematical model, daily profiles were formed for the joint operation of a PV-plant and BESS for a whole year. The analysis of the obtained daily profiles for the whole year showed, that for a day with maximum solar irradiation, in order to transfer 20% of PV-plants generated electrical energy, the discharge power of the BESS should be about 37% of the installed capacity of the inverters of the PV-plants. Thus, for 2040, with the installed capacity of PV-plants at the level of 11 GW, the total capacity of BESS should be 4 GW, and their charging capacity – 16 GWh.Using a mathematical programming model, determining the optimal structure and loading of power units of the power system when covering the daily schedule of electrical loads for each day of the year, it was determined that the introduction of BESS in PV-plants affects the performance of the power system as a whole. The transfer of 20% of the peak generation capacity of PV-plants with an installed capacity of 11 GW at the level of 2040 leads to: an increase in the production of electricity from nuclear power plants by 8% with an increase in the number of power units with an installed capacity of 1000 MW; the volume of electricity production at coal-fired thermal power plants is reduced by 20%; the generation volumes of pumped storage power plants are reduced by 4.5% and the discharge volumes of the system-scale storage systems are reduced by 57%. Reducing coal consumption by 19% leads to a 15‒19% reduction in emissions of carbon dioxide, sulfur oxides, nitrogen oxides and dust, which are important results for achieving environmental goals of Ukraine.